Safeguarding adults: from realism to ritual. Issue 6 (12th December 2016) - Yoeli, Heather; Lonbay, Sarah P.; Morey, Sarah; Pizycki, Lara
Abstract : Purpose: The landscape of adult social care, and in particular of adult safeguarding, has shifted considerably over the last decade. Alongside policy changes in the responses to adult abuse, there have been shifts in professional and public understanding of what falls within the remit of this area of work. This results, arguably, in differing understandings of how adult safeguarding is constructed and understood. Given the increasing emphasis on multi-agency inter-professional collaboration, service user involvement and lay advocacy, it is important to consider and reflect on how both professionals and lay people understand this area of work. The paper aims to discuss these issues. Design/methodology/approach: This study employed Augusto Boal's model of Forum Theatre to explore how a variety of professional and lay groups understood, related to and engaged with how the Care Act 2014 defines and describes "adult safeguarding". Findings: Lay participants responded to the scenario in a variety of ways, upholding the construct validity of "adult safeguarding" and the authority of the social worker. Social care and health practitioners sought orderly, professionalised and sometimes ritualistic solutions to the "adult safeguarding" scenario presented, seeking carefully to structure and to manage lay involvement. Inter-professional collaboration was often problematic. The role of lay advocates was regarded ambiguously and ambivalently. Originality/value: This paper offers a number of practice and research recommendations. Safeguarding practitioners could benefit from more effective and reflexive inter-professional collaboration. Both practitioners and service users could benefit from the more thoughtful deployment of the lay advocates encouraged within the Care Act 2014 and associated guidance.